4‐Cyanoresorcinol‐Based Bent‐Core Mesogens with Azobenzene Wings: Emergence of Sterically Stabilized Polar Order in Liquid Crystalline Phases. (27th November 2013) - Alaasar, Mohammed; Prehm, Marko; May, Kathrin; Eremin, Alexey; Tschierske, Carsten
<x xml:space="preserve">Abstract</x> A new series of azobenzene containing bent‐core molecules incorporating 4‐cyanoresorcinol as the central core unit exhibiting cybotactic nematic, rectangular, columnar, and different types of tilted smectic (SmC) phases are synthesized. The mesophase behavior and phase structures are characterized in bulk and freely suspended films using a variety of experimental techniques. Depending on the chain length and temperature a series of different mesophases is observed in these compounds, ranging from cybotactic nematic via paraelectric SmC phases, polarization randomized SmCsPR phases to ferroelectric and antiferroelectric SmC phases, associated with increasing size and correlation length of the polar domains. Spontaneous formation of chiral domains is observed in the paraelectric SmC and the SmCsPR phases and discussed in relation with superstructural chirality, bend elastic constants, and surface effects.